Pengaruh Pengetahuan Zakat, Motivasi Membayar Zakat dan Sosial Ekonomi Terhadap Kesediaan Dosen Universitas Tridinanti Palembang Dalam Membayar Zakat Profesi Melalui Pemotongan Gaji - Frastuti, Melia; Trinanti Oktavia, Deta (Akuntansi dan Manajemen, 2019)
The problem of zakat in this country actually started from the low awareness of the muzakki (people who issue zakat) to do it and the low of public trust in the Amil Zakat Agency and the Zakat Institusion, even though any expertise and wok that is lawful, whether done alone or related to other parties, sucs as an employee, if thei income reach the nishab, then zakat must be issued. This study aims to see how the knowledge of zakat, motivation and social-economic on the willingness University of Tridinanti Palembang lecturers in paying professional zakat through salary deductions. The population in this study was 190 lecturers at the University of Tridinanti Palembang (UTP). The sampel technique used was purposive sample with the criteria of lecturers who had obtained lecturer certification, amounting to 121 people from 4 fakulties at UTP. The data analysis used is using multiple linear regressions analysis. The results of the study state that the knowledge of zakat, zakat motivation and social- economic have a positive.